INDIAN DEMOCRACY: THE CONCEPT OF ’ONE NATION, ONE ELECTION’ - Meena, Pooran Mal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The concept of ’One Nation, One Election’ in India is a proposal to hold simultaneous elections to the state assemblies and the Lok Sabha. The idea is proposed to save the country’s resources, time and cost, reduce administrative burden and ensure stability of governance. Its benefits include reduction in election expenditure, ease of policy-making, and public convenience. However, its implementation faces problems such as constitutional amendment, political consensus, technical difficulties, and the challenge of snap elections. Its impact on Indian democracy can be positive, provided it is implemented keeping in mind the diversity of the country and the constitutional framework. Overall, this concept can make the democratic process more robust and inclusive.